Pharmacokinetics of Tranexamic Acid in Neonates, Infants, and Children Undergoing Cardiac Surgery with Cardiopulmonary Bypass. (April 2015) - Wesley, Mark C.; Pereira, Luis M.; Scharp, Laurie A.; Emani, Sitaram M.; McGowan, Francis X.; DiNardo, James A.
Abstract : Background: Tranexamic acid (TXA) is one of the most commonly used antifibrinolytic medications in children undergoing repair of congenital heart defects. However, a pharmacokinetics analysis of TXA has never been performed in neonates or young children undergoing complex cardiac surgeries using cardiopulmonary bypass, hypothermia, circulatory arrest, and ultrafiltration. A comprehensive pharmacokinetics study was performed in this patient population. Methods: Fifty-five patients ranging from 2 days through 4 yr old were categorized into three groups: children less than 2 months old, infants 2 months to 1 yr old, and children greater than 1 yr old and weighing up to 20 kg. TXA was given as a bolus of 100 mg/kg followed by an infusion of 10 mg · kg −1 · h −1 throughout the surgery. A dose of 100 mg/kg was placed in the cardiopulmonary bypass prime. A total of 16 to 18 samples were obtained from all patients throughout surgery. Plasma TXA concentrations were measured by high-performance liquid chromatography and modeled under a nonlinear mixed-effects framework with a two-compartment structural model. Results: Cardiopulmonary bypass had a statistically significant impact on all pharmacokinetic parameters. Age was a better covariate than body weight, affecting both the distribution and the elimination of TXA. However, weight performed well in some cases. Other covariates including body surface area, pump prime volume, ultrafiltrate volume, and body temperature did not improve the model. Conclusions: This TXA pharmacokinetic analysis is reported for the first time in neonates and young children undergoing complex cardiac surgeries with cardiopulmonary bypass. Dosing recommendations are provided as guidance for maintaining desired target concentrations. Abstract : Tranexamic acid pharmacokinetics were determined during cardiac surgery in 55 children categorized into three age groups: less than 2 months old; 2 months to 1 yr old; and more than 1 yr old and weighing up to 20 kg. Dosing recommendations were modeled for each age group for plasma concentrations of 20, 60, and 150 μg/ml. The safe and effective tranexamic acid concentration range needs to be better defined.